BIG DATA ANALYTICS FOR SAFE AND SECURE CITY - Setiyono
According to the UN around 68% of the world population in 2050 will live in urban areas. With the increasing population of the city every year, it will cause several problems that arise, among others, problems of security, health, education, traffic congestion, energy, and so on. Smart solutions are needed from the city government to overcome this problem. One solution is smart city. To realize a smart city one of the main challenges is the solution to the problem of security.